The effects of wheat middlings, particle size, complete diet grinding, and diet form on nursery and finishing pig growth performance - De Jong, Jon Andrew (Kansas State University, 2013)
Seven experiments using a total of 2,997 nursery and finishing pigs were used to determine the effects of: 1) dietary wheat middlings (midds), dried distillers grains with solubles (DDGS), and NE diet formulation on nursery pig growth performance; 2) corn particle size, complete diet grinding, and diet form on finishing pig growth performance, and carcass characteristics, and 3) particle size, complete diet grinding, and diet form on nursery pig growth. Experiments 1-4 evaluated dietary wheat middlings at levels of up to 20% of the diet for 7 to 23 kg pigs. Increasing dietary midds decreased growth performance but mainly when 10% of more was added. Balancing diets containing 10 or 20% midds on a NE basis had no significant effects on performance compared with not adjusting for NE of the diet. In Exp. 5, the effects of decreasing particle size, complete diet grinding, and diet form were evaluated on finishing pig growth performance, and carcass characteristics. Diet form × portion ground interactions existed for ADG, ADFI, and HCW as grinding the complete diet in meal form was detrimental to performance but advantageous to performance when diets were fed in pelleted form. Reducing the particle size of corn improved G:F and caloric efficiencies. Pelleting the diet improved ADG, G:F, caloric efficiencies, HCW, and loin depth. Experiment 6 evaluated varying particle sizes, diet form, and complete diet grinding on nursery pig growth performance. Pigs fed pelleted diets had improved ADG, G:F, and caloric efficiencies. Fine grinding corn or the complete diet with high by-products diet decreased ADG, ADFI, G:F, and final BW. Experiment 7 evaluated varying particle sizes of corn and DDGS, diet form, and complete diet grinding on nursery pig growth performance. Pigs fed finely ground corn had decreased ADFI when the diet was fed in pellet form and more severe reductions in ADFI when diets were fed in meal form resulting in a diet form × corn particle size interaction. Pigs fed pelleted diets had decreased ADG, ADFI, G:F and final BW, but improved caloric efficiencies. Finely grinding corn decreased ADG, and feeding DDGS decreased ADG, ADFI, and NE caloric efficiency.
Keywords: Wheat middlings; Pelleting; Particle size; Nursery pig; Finishing pig; Growth; Animal Sciences (0475)